Pediatric Fabry disease - Ries, Markus; Gupta, Surya N.; Moore, David F.; Sachdev, Vandana; Quirk, Jane M.; Murray, Gary J.; Rosing, Douglas R.; Robinson, Chevalia; Seib-Schaefer, Ellen; Gal, Andreas; Dambrosia, James M.; Garman, Scott C.; et al. (Pediatrics, 2005)
Background. Fabry disease is an underdiagnosed, treatable, X-linked, multisystem disorder. - Objectives. To test the hypothesis that quality of life and sweating are decreased among pediatric patients with Fabry disease, compared with control subjects, and to provide quantitative natural history data and novel clinical end points for therapeutic trials. - Design. Prospective, cross-sectional, observational study. - Setting. Referral to the National Institutes of Health. - Participants. Twenty-five male children with Fabry disease (mean age: 12.3 ± 3.5 years) and 21 age-matched control subjects. - Main Outcome Measures. Quality of life (measured with the Child Health Questionnaire) and sweating (assessed with the quantitative sudomotor axon reflex test). - Results. Quality of life scores for pediatric patients <10 years of age with Fabry disease, compared with published normative values, were 55 ± 17 vs 83 ± 19 for bodily pain and 62 ± 19 vs 80 ± 13 for mental health. Bodily pain scores for patients ≥10 years of age were 54 ± 22 vs 74 ± 23. Sweat volume in the Fabry disease group was 0.41 ± 0.46 μL/mm2, compared with 0.65 ± 0.44 μL/mm2 in the control group. Renal function, urinary protein excretion, and cardiac function and structure were normal for the majority of patients. The 3 patients with residual α-galactosidase A activity ≥1.5% of normal values were free of cornea verticillata and had normal serum and urinary globotriaosylceramide levels. All other children had glycolipid levels comparable to those of adult patients with Fabry disease. Acroparesthesia and cardiac abnormalities were generally present before anhidrosis and proteinuria. Mapping of the missense mutations on the crystallographic structure of α-galactosidase A revealed that the mutations were partially surface-exposed and distal to the active site among individuals with residual enzyme activity. Mutations associated with left ventricular hypertrophy (defined as left ventricular mass index of >51 g/m2.7) were localized near the catalytic site of the enzyme. - Conclusions. Despite the absence of major organ dysfunction, Fabry disease demonstrates significant morbidity already in childhood. We have identified important, potentially correctable or preventable, outcome measures for future therapeutic trials. Prevention of complications involving major organs should be the goal for long-term specific therapy.